Reinforcement of Natural Rubber with Core-Shell Structure Silica-Poly(Methyl Methacrylate) Nanoparticles. (17th August 2011) - Wang, Qinghuang; Luo, Yongyue; Feng, Chunfang; Yi, Zhifeng; Qiu, Quanfang; Kong, L. X.; Peng, Zheng
Abstract : A highly performing natural rubber/silica (NR/SiO2 ) nanocomposite with a SiO2 loading of 2 wt% was prepared by combining similar dissolve mutually theory with latex compounding techniques. Before polymerization, double bonds were introduced onto the surface of the SiO2 particles with the silane-coupling agent. The core-shell structure silica-poly(methyl methacrylate), SiO2 -PMMA, nanoparticles were formed by grafting polymerization of MMA on the surface of the modified SiO2 particles via in situ emulsion, and then NR/SiO2 nanocomposite was prepared by blending SiO2 -PMMA and PMMA-modified NR (NR-PMMA). The Fourier transform infrared spectroscopy results show that PMMA has been successfully introduced onto the surface of SiO2, which can be well dispersed in NR matrix and present good interfacial adhesion with NR phase. Compared with those of pure NR, the thermal resistance and tensile properties of NR/SiO2 nanocomposite are significantly improved.